Salt and drought stresses in safflower: a review - Hussain, Muhammad Iftikhar; Lyra, Dionyssia; Farooq, Muhammad Shahid; Nikoloudakis, Nikolaos; Khalid, Nauman (My University, 2016)
Safflower is one of the oldest cultivated crops, usually grown at a small scale. Safflower is grown for flowers used for coloring, flavoring foods, dyes, medicinal properties, and livestock feed. Safflower is underutilized but gaining attention due to oil yield potential and the ability to grow under high temperatures, drought, and salinity. Salinity and drought have negative effects by disrupting the ionic and osmotic equilibrium of the plant cells. The stress signal is perceived by membranes then transduced in the cell to switch on the stress responsive genes. This review discusses on stress tolerance mechanisms in safflower. Strategies are proposed for enhancing drought and salt resistance in safflower.
Keywords: Compatible solutes; Drought stress; Growth; Management; Osmotic ionic; Salinity stress; Stress tolerance